(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2016)
The main objective of competition law is to ensure that the market is functioning properly and resources are allocated efficiently in society. Competition law is often perceived as a form of consumer protection law which promotes the interest of the end consumer, and as a law that protects the interest of small and medium enterprises. Competition law in its true sense is part of commercial law that regulates the activities of enterprises in the market. It is not a consumer law which automatically promotes or takes into consideration the interest of end consumers. It is also applicable to all enterprises, regardless of size, big or small. Nevertheless, there are many provisions in competition law which may provide indirect benefit to end consumers and small enterprises. This article provides an overview of the structure of competition law in Malaysia. The main objective of this article is to analyze the implementation of the Malaysian Competition Act 2010 and its roles in protecting and promoting the interest of consumers and small enterprises. Keywords: competition, competition law, consumer, small and medium enterprises